MIDDLE PALEOZOIC SUBDUCTION BELTS: THE LEADING FACTOR IN THE FORMATION OF THE CENTRAL ASIAN FOLD-AND-THRUST BELT - Filippova I.B.; Bush V.A.; Didenko A.N. (My University, 2001)
The Paleozoic fold-and-thrust belt, confined between the European, Siberian, Tarim, and North China Precambrian continents, results from a complex evolution of the Paleo-Asian Ocean. At the end of the Ordovician, the Kazakhstan-Kyrghyz continent, originating from the accretion of island arcs and Gondwanan continental fragments, divided the Paleo-Asian Ocean into four oceanic basins, Uralian, Turkestan, Junggar-Balkhash, and Ob-Zaisan. The Middle to Late Paleozoic history of these oceanic basins, which closed completely in the terminal Carboniferous to Permian, is portrayed in eight detailed, 1:10,000,000 scale, palinspastic reconstructions for the Early Silurian (430 Ma), Early Devonian (Emsian, 390 Ma), Middle Devonian (Givetian, 380 Ma), Late Devonian (Famennian, 360 Ma), Early Carboniferous (late Visean to Serpukhovian, 330 Ma), early Late Carboniferous (305 Ma), Early Permian (280 Ma), and Late Permian (255 Ma) time slices. These reconstructions draw on 1:2,500,000 scale sedimentologic-paleogeographic maps and paleomagnetic measurements from ancient continents and Variscan orogenic zones of the Urals, Kazakhstan, Tien Shan, Junggaria, and Altay. The shrinking and collision-induced closure of the oceans were ensured by the three large and long-lived (100-130 m.y.) Urals-Tien Shan, Junggar, and Siberian subduction belts, spanning thousands of kilometers, whose polarities remained stable. The belts were represented by systems of roughly parallel and branching subduction zones, each with a 10-30 m.y. lifespan, plunging beneath the Kazakhstan-Kyrghyz and Siberian continents. Taken together, they constituted a system that diverged in a southwesterly direction and ensured differential rotations of the European, Siberian, and Kazakhstan-Kyrghyz continents. The Urals-Turkestan belt began to form at the beginning of the Silurian, and the Siberian and Junggar belts, at the beginning of the Devonian. The subduction belts ceased to exist as they were crushed between continents during a general collision that set on in the second half of the Devonian and in which the Junggar belt became involved prior to the beginning of the Permian. Geologic and paleomagnetic evidence points to oblique motions of oceanic plates being consumed in the subduction belts and, accordingly, to an oblique collision in the Urals and South Tien Shan foldbelts that propagated through time and space to finally give rise to large-scale post-collisional lengthwise strike slips. We believe the subduction belts to be surface manifestations of descending mantle convection flows that drove the long-lasting sinking of oceanic plates into the mantle.
Keywords: CENTRAL ASIAN AND URALS-MONGOLIA FOLD-AND-THRUST BELTS; PALEO-ASIAN; URALIAN; TURKESTAN; JUNGGAR--BALKHASH; OB--ZAISAN PALEOCEANS; SUBDUCTION ZONES; OBLIQUE COLLISION; PALINSPASTIC RECONSTRUCTIONS; MIDDLE TO LATE PALEOZOIC; Paleozoic; Paleozoic; Палеозой